GW24-e1001 Effects of advanced glycation end products on function and angiogenesis of adipose tissue-derived stem cells and protective effects of Danhong injection. (1st October 2013) - Feng, Wu; Zhiqing, He; Ruizhen, Ji; Xin, Wang; Zonggui, Wu; Chun, Liang
Abstract : Objectives: To investigate the effects of N ε -(carboxymethyl) Lysine albumin (CMLs), a primary advanced glycation end products isoform in diabetic body, on function and angiogenesis of adipose tissue-derived stem cells (ADSCs) and protective effects of Danhong injection. Methods: ADSCs were obtained by combination with enzymatically digestion and centrifugation, and then were identified to observe cultured cells' morphology and induce differentiation towards adipocytes, osteocytes and chondrocytes. The cells were exposed to 5 different interventions respectively for 24 hours, including PBS, 60 μg/mlBSA, 60 μg/ml CML-BSA, 0.5 ul/ml DH and 60 μg/mlCML-BSA + 0.5 ul/ml DH. The proliferation capability of such cells were evaluated using WST-1 assay, migration ability were explored by transwell assay, the apoptoticrates were investigated by FCM, secreted VEGF in culture supernatant were measured by ELISA, and angiogenesis of such cells was observed in matrigel invitro. Results: Compared with the BSA control group, proliferation, migration and secretion capability of ADSCs were inhibited by stimuli with CML-BSA (n = 6, P < 0.05), but the apoptosis of such cells were promoted. Finally, angiogenesis of ADSCs was significantly inhibited. DH (0.5 ul/ml) could promote proliferation, migration and secretion capability but inhibit apoptosis of ADSCs (n = 6, P < 0.05) vs PBS, and furthermore partiallyreverse the negative effects of CML-BSA (60 μg/ml) on ADSCs (n = 6, P < 0.05). Conclusions: CMLs could significantly inhibit proliferation, migration, but promote apoptosis and reduce VEGF expression and secretion of ADSCs. DH injection would partially reverses the negative effects of CMLs. CMLs could significantly inhibit angiogenesis of ADSCs, which would partially reversed by DH injection.